Spatial-temporal evolution of urban heat Island in Xi'an from 2006 to 2016. (April 2019) - Liu, Suhua; Zang, Zhenfeng; Wang, Wenchuan; Wu, Yueru
Abstract: During the rapid development of urbanization, the urban heat island (UHI), becomes one of the major urbanization progress problems that affects the environmental, social and ecology profoundly. Analyzing the UHI can help understanding the UHI status and the physical characteristics of cities, and is significant to provide ecosystem management plans and mitigation strategies for the UHI. By utilizing the MODIS LST products, Landsat series data and the ecological regionalization data, and applying the corresponding methods to derive the NDVI, the fractional vegetation cover (Fv ) and the LST normalizations results, the study conducted the spatial-temporal evolution of the UHI in Xi'an from 2006 to 2016. The main work includes analyzing the spatial evolution characters, analyzing the temporal evolution characters and exploring the relationship between LST and vegetation cover. Spatial evolution results showed that the UHI to the north of the urban land control line in 2016 became intensified and enhanced in the form of increasing the LST and the UHI zone. As for the temporal evolution, the Low Temperature Zone and Sub-low Temperature Zone had little changes and corresponded with the urban land control line, and the Medium Temperature Zone decreased on large area while the Sub-high Temperature Zone increased on large area, when compared results of 2006 with that of 2016. The relationship between LST and vegetation cover indicated that increasing vegetation cover had a certain active role for reducing LST and mitigating the UHI. The positive intervention and guidance of the government on the ecological protection can reduce the UHI, effectively. Highlights: The UHI to the north of urban land control line became intensified and enhanced. The UHI intensified and enhanced in the form of increasing the LST and the UHI zone. Increasing vegetation cover is useful for reducing LST and mitigating the UHI. Intervention and guidance of the government can reduce the UHI, effectively.